Electrocardiographic manifestations in female team handball players: analyzing ECG changes in athletes - Malmgren, A.; Trägårdh, E.; Gudmundsson, P.; Kjellström, B.; Stagmo, M.; Dencker, M. (Frontiers in Sports and Active Living, 2024)
Introduction Long-term intense training leads to structural, functional, and electrical remodeling of the heart. How different sports affect the heart has not been fully investigated, particularly for female athletes. The aim of the present study was to investigate the morphology of 12-lead resting electrocardiogram (ECG) in elite female handball players compared to non-athlete female subjects. Potential changes will be explored to see if they could be explained by differences in cardiac dimensions and exercise hours. Materials and methods A cross-sectional study of 33 elite female team handball players compared to 33 sex and age-matched, non-athletic controls (age range 18–26 years) was performed. All participants underwent a resting 12-lead ECG and an echocardiographic examination. ECG variables for left ventricular hypertrophy and durations were evaluated and adjusted for cardiac dimensions and exercise hours using ANCOVA analysis. A linear regression analysis was used to describe relation between echocardiographic and ECG measures and exercise hours. Results The female handball players had larger cardiac dimensions and significantly lower heart rate and QTc duration (Bazett's formula) as well as increased QRS and QT durations compared to controls. The 12-lead sum of voltage and the 12-lead sum of voltage ∗ QRS were significantly higher among handball players. Changes in ECG variables reflecting the left ventricle could in part be explained by left ventricular size and exercise hours. Correlation with exercise hours were moderately strong in most of the echocardiographic measures reflecting left ventricular (LV), left ventricular mass (LVM), left atrium (LA) and right atrium (RA) size. Poor to fair correlations were seen in the majority of ECG measures. Conclusions Female team handball players had altered ECGs, longer QRS and QT durations, higher 12-lead sum of voltage and 12-lead sum of voltage ∗ QRS as well as shorter QTc (Bazett's formula) duration compared to non-athletic controls. These findings could only partly be explained by differences in left ventricular size. Despite larger atrial size in the athletes, no differences in P-wave amplitude and duration were found on ECG. This suggest that both structural, and to some degree electrical remodeling, occur in the female team handball players' heart and highlight that a normal ECG does not rule out structural adaptations. The present study adds knowledge to the field of sports cardiology regarding how the heart in female team handball players adapts to this type of sport.